Differences in the course of coxitis in men and women with early axial spondyloarthritis - E. M. Agafonova; Sh. Erdes; T. V. Dubinina; A. B. Demina; A. V. Smirnov (Научно-практическая ревматология)
Introduction. Currently, there is a small number of studies devoted to the differences in the manifestations of axial spondyloarthritis (axSpA) in men and women, and there are no studies assessing the frequency of coxitis in axSpA in patients of different sexes. The purpose of the study is to compare the main manifestations of coxitis in axial spondyloarthritis in men and women. Material and methods. The study was conducted on the Moscow Cohort of Early SpondyloArthritis (CoRSAr), which currently includes 175 patients. Their age at the time of inclusion in the cohort was on average 28.5±5.8 years, the duration of the disease was 24.1±15.4 months. 92.6% of patients were positive for HLA-B27 (human leukocyte antigen B27). All patients were assessed for pain in the hip joints (HIP) using a numerical rating scale (NRS) (0–10), and pelvic radiography, magnetic resonance imaging (MRI) and ultrasound examination of the Hip joint were performed. An increase in the cervical-capsular distance (NCD) of more than 7.0 mm was considered a sign of coxitis according to ultrasound data. When analyzing MRI results, signs of coxitis were considered to be synovitis and/or osteitis of the femoral head or acetabulum. X-ray changes in the hip joint were assessed using the BASRI-hip index (Bath Ankylosing Spondylitis Radiology Hip Index). Results and discussion. Among the 175 patients, there were 97 (55.4%) men and 79 (44.6%) women. At the time of inclusion in the study, women were older than men (p<0.01), while the duration of the disease in men and women was the same and averaged about 2 years. In men, X-ray changes in the hip joint were more common than in women (in 7.2% and 1.3% of cases, respectively; p<0.05). Clinical signs of coxitis were detected in 54 (55.7%) men and 41 (51.9%) women, while the level of pain according to the NRS in women averaged about 2, and in men – about 3 points (p>0.05). According to ultrasound data, coxitis was detected in 15 (18.9%) women and 27 (27.8%) men; NCD averaged 6.2 mm in men and 5.9 mm in women (p>0.05). In men, signs of damage to the hip joint according to MRI were more common than in women (in 27.8% and 15.1% of cases, respectively; p<0.05). The level of C-reactive protein (CRP) in men was also higher than in women (on average 12.8 and 4.3 mg/l, respectively; p<0.05). Conclusion. Women develop axSpA at a later age than men, and the latter are more likely to have HLA-B27, MRI features of coxitis, and higher levels of CRP.